Modular line-selector unit for enabling selective-scan driving in conventional oxide TFT scan drivers - Minjae Jeong; Young Wook Kim; Ki Taeg Shin; Hoon Jeong; Jeong Ki Park; Hyun Jae Kim (Journal of Information Display)
This paper proposes a novel circuit called the Line-Selector Unit (LSU) that enhances conventional oxide thin-film-transistor (TFT) scan drivers. The LSU, consisting of four transistors, one capacitor, and three additional control signals, allows a traditional scan driver to generate scan signals only in the selected area. A 12-stage scan driver with the LSU was fabricated using oxide TFTs, and experimental results demonstrate that the LSU operates regardless of the position and size of the selected area. Moreover, the LSU does not experience voltage stress during conventional scan driving and enhances reliability by employing an optimized driving method that distributes positive voltage bias stress during selective-scan driving. In addition, the LSU consumes only 0.1% of the total scan driver power consumption, making it a highly compatible and energy-efficient solution for low-power display applications.